Kasih Sejati: Memahami Misi Secara Teks, Konteks, dan Komunitas Berdasarkan Yohanes 17:18 Pada PTT/AK - Karlau, Sensius Amon (Jurnal Teologi Praktika, 2020)
The existence of God is in essence impossible to shift, but, in fact seems to experience a shift that appears in human efforts to respond to the mission call. Efforts to "narrow" the meaning, purpose and impact of understanding the "true love and mission" for His people here are in contrast to God's love that cannot be separated from His essence. God himself wants His love to be part of His ransom people, so this is where "mission" becomes the logical implication of God's existence as a mission initiator that has been, is being, and continues to be done through His chosen people in every age in (community). The author used qualitative method with text and language analysis approaches. Based on research results in the "text" it can be understood that God's love enables Him to send His only begotten Son to fulfill His mission. Then in His grace; The Son continues the Father's mandate to disciples to become a "community" sharing the love of God the Father. This task is then passed on to the present generation specifically for graduates of Theological/Christian Religious College.